EFISIENSI PEMASARAN NANAS (Ananas Comosus (L) Merr) DI DESA PANGKUL KECAMATAN CAMBAI KOTA PRABUMULIH - Ursula Damayanti; Sri Rahayu Endang Lestari (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to determine the efficiency and pattern of pineapple marketing channels in Pangkul Village, Cambai District, Prabumulih City. This research was carried out from March to April 2023. The sampling method used purposive sampling of 16 farmers, 1 collector and 6 retailers. To determine the marketing efficiency of pineapples, quantitative analysis is used, while to determine the pineapple marketing channel patterns, descriptive analysis is used. The research results show that there are three (3) marketing channel patterns for pineapple fruit, namely: channel pattern I. Farmers sell their harvest to collectors and collectors sell to factories. Channel pattern II Farmers sell their crops to retailers and retailers sell to final consumers. Channel III pattern: farmers sell their crops to collectors, then collectors sell to retailers and retailers sell to final consumers. Of the three pineapple marketing channel patterns, it turns out that marketing pattern I is efficient compared to marketing patterns II and III. Judging from the margin and farmer's share results, marketing channel pattern I is said to be efficient, because the marketing margin value is lower and the farmer's share is higher, namely 52. 8% of marketing channel patterns II and III. The highest profit is found in marketing channel pattern III IDR 10,739.7/piece. In marketing channel pattern I, the profit obtained by collectors is IDR 1,782/piece, marketing costs IDR 577/piece and margin IDR 2,360/piece. In marketing channel pattern II, the retailer's profit is IDR 10,539.7/piece, marketing costs IDR 1,626.3/piece, and a margin of IDR 4,055.33/piece.